FEATURES OF THE COURSE OF BRONCHO-OBSTRUCTIVE SYNDROME IN CHILDREN WITH THYMOMEGALY DEPENDING ON THE LEVEL OF VITAMIN D (Proceedings of International Educators Conference, 2024)
This study examines the influence of vitamin D levels on the progression of broncho-obstructive syndrome in children diagnosed with thymomegaly. By evaluating clinical and laboratory data, the research aims to determine how varying concentrations of vitamin D correlate with the severity and management outcomes of broncho-obstructive symptoms in these pediatric patients. Statistical analyses were conducted to provide a detailed understanding of these correlations.